HISTORISITAS DAN MISI ESENSIAL HUKUM WARIS ISLAM - Muhammad Adib (LP3M IAI Al-Qolam Malang, 2017)
The Islamic hereditary law, which has been regulated in the Islamic law resources (manshush), has been raising a polemic. Some Moslem scholars regarded the nash as ta’abbudi and therefore cannot be interfered, while others saw such concept of ta’abbudi is a deviation from the basic nature as well as the main goal of syari’ah. Through this, the claim that nash is not reasonable and reconceivable has fell. This lattest thing is urgently emphasized in order to revitalize the spirit of syari’ah in the human life. This working paper explores the essential mission of Islamic hereditary law in the historical point of view, beginning from the pre-Islamic era to the modern society. Keywords: Islamic hereditary law, nash, Arabic pre-Islamic tradition, development